1976
DOI: 10.1136/bmj.2.6042.965
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of preterm delivery to perinatal mortality.

Abstract: A detailed retrospective analysis was made of the records of 486 preterm infants, who accounted for 5-100 of all births during 1973 and 1974. Whereas preterm delivery did not contribute to perinatal mortality in terms of stillbirth, it outweighed all other causes in terms of early neonatal deaths. Preterm birth was responsible for 85'o of the early neonatal deaths not due to lethal congenital deformities. Early neonatal mortality rates were closely linked both to gestational age and birth weight and to the rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
67
0
3

Year Published

1983
1983
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 305 publications
(72 citation statements)
references
References 7 publications
2
67
0
3
Order By: Relevance
“…36,37 Therefore, the significant increased risk for preterm births found after in utero exposure to SGAs (OR, 1.85; 95% CI, 1.20-2.86) may pose a significant health care issue. Furthermore, a study by Russell et al 38 (2007) reported that preterm births use significant amounts of health care resources, causing longer hospital stays, and almost 50% of the costs of infant hospitalizations.…”
Section: Discussionmentioning
confidence: 98%
“…36,37 Therefore, the significant increased risk for preterm births found after in utero exposure to SGAs (OR, 1.85; 95% CI, 1.20-2.86) may pose a significant health care issue. Furthermore, a study by Russell et al 38 (2007) reported that preterm births use significant amounts of health care resources, causing longer hospital stays, and almost 50% of the costs of infant hospitalizations.…”
Section: Discussionmentioning
confidence: 98%
“…Preterm labor occurs in 5%-10% of all pregnancies and accounts for 70% of neonatal morbidities and mortality not attributable to congenital anomalies [1]. Long-term morbidities, including neurological handicap and learning difficulties, impose a substantial cost on the health care and education systems as well as placing emotional hardship and stress on families [2].…”
Section: Introductionmentioning
confidence: 99%
“…Complications resulting from idiopathic preterm birth, defined as delivery before 37 weeks of gestation, account for the majority of perinatal deaths of infants without anomalies in developed nations (1,2). Preterm premature rupture of the membranes (PPROM) 1 occurs in ϳ1% of all pregnancies and is associated with 30 -40% of preterm deliveries (3).…”
mentioning
confidence: 99%